Empathy in Medical Ethics: A Systematic Review of Its Role in Healthcare Integrity: Empathy in Medical Ethics - Noor, Sana; Ali, Anusha Nauroz; Arif, Faryal; Ravail, Aneeqa; Ihsan, Arbia; Siddique, Izza (Pakistan Journal of Health Sciences, 2026)
Empathy is the capacity to relate to and reflect on the emotions of others. Empathy improves outcomes in healthcare environments if one delivers compassionate, patient-centered treatment. Objectives: This systematic review examines empathy’s role in medical ethics, its impact on patient outcomes, and barriers to its practice. Methods: This systematic review used PRISMA rules and used major databases, including PubMed, Scopus, Web of Science, and the Boolean search string. The studies included were published in the English language between 2002 and 2023. Among the search terms used were "empathy," "medical ethics," "healthcare settings," and "patient-centered care". Fourteen studies in all fit the inclusion criteria. Comprising medical schools, hospitals, clinics, and community health centers, among other healthcare environments, the studies were published during the selected time bracket. Results: According to the review, Empathy correlates with Ethical practice: Supports beneficence, autonomy, and reduces litigation. Patient outcomes are related to Higher satisfaction and treatment adherence when treated by an empathetic doctor. Barriers are Burnout and empathy decline during training. Interventions like Role-playing and neuroscience-based curricula improved empathy. Conclusions: Medical ethics cannot be valued without empathy. Encouragement of empathy in healthcare environments will help to raise patient outcomes, satisfaction, and the general standard of quality of treatment. Empathy is a measurable, teachable skill critical to ethical practice. Address burnout and integrate training to sustain healthcare integrity.